Yeasts associated with the worker caste of the leaf-cutting ant Atta cephalotes under experimental conditions in Colombia - Giraldo, Carolina; Chaves-López, Clemencia; Tofalo, Rosanna; Angrisani, Roberto; Rodrigues, Andre [UNESP]; Montoya-Lerma, James (Springer Nature, 2022)
Yeasts isolated from the worker caste of the Colombian leaf-cutting ant, Atta cephalotes (Hymenoptera: Myrmicinae) were cultured and identified by molecular methods. Abundant, persistent, and omnipresent species were classified as “prevalent”. Experimental data were compared with information gathered from published reports on the yeast species composition in other leaf-cutting ant species. Diversity analysis was conducted using diversity values (q0, q1, and q2) to compare the richness and abundance of yeasts present in different leaf-cutting ant species. Clustering analysis was carried out to assess the similarity of yeast community according to ant species. The yeast species composition was highly variable among the ant species. A. laevigata and A. capiguara showed the highest degree of similarity and differed from the group composed by A. cephalotes, A. sexdens, A. sexdens rubropilosa, and A. texana. The isolation of dominant yeasts in different ant castes within the different compartments of a colony strongly suggests that the identified microorganisms are not transient but are native to the soil surrounding ant colonies and the substrates used by the ants to grow their fungal cultivars. It is apparent that the ant-fungus mutualism does not operate in an environment devoid of other microbes, but rather that the association must be seen within the context of a background of other microorganisms, particularly the dominant yeasts.
Keywords: Diversity; Division of labor; Microbiota; Mutualism; Tropical ants